Recent Attitudes toward ADHD in the Broader Community: A Systematic Review. Issue 4 (February 2022) - Bisset, Matthew; Winter, Leanne; Middeldorp, Christel M.; Coghill, David; Zendarski, Nardia; Bellgrove, Mark A.; Sciberras, Emma
Objective: This review aimed to understand the broader community's attitudes toward ADHD, which could facilitate public health interventions to improve outcomes for individuals with ADHD. Methods: A standardized protocol identified peer-reviewed studies focusing on attitudes of broader community samples, published from January 2014 to February 2020 (inclusive). Results: A total of 1, 318 articles were screened and 10 studies were included, examining attitudes of broader community samples from Australia, Sweden, Germany, Finland, Korea, Indonesia, and the United States. Findings revealed that broader community samples displayed varying degrees of ADHD-related knowledge, negative attitudes (that ADHD is over-diagnosed; that pharmacological treatment is not acceptable; that those with ADHD are more likely to exhibit poor behavior), and a desire for maintaining social distance from individuals with ADHD. Conclusion: Findings suggest that community attitudes are generally negative toward those with ADHD. Targeted mental health literacy could provide an important avenue for improving the broader community's attitudes toward those with ADHD.